Promoting Effect of L-tyrosine Supplement on New Zealand Rabbit Bucks' Performance and Reproduction Through Upregulation of Steroidogenic Markers - Mahmoud, Shawky; Saad, Michel; El-Shehawi, Ahmed M.; Farrag, Foad; Abo Ghanima, Mahmoud M.; Dawood, Mahmoud A. O.; Shukry, Mustafa (Frontiers in Veterinary Science, 2020)
Delayed puberty and lower fertility are among the most challenging concerns in rabbit development during the summer season. This study was, therefore, aimed at enhancing male NZ rabbits' performance by using L-tyrosine. Thirty male, New Zealand rabbits, were employed for this purpose at the age of 60 days. Rabbits were divided accidentally into two groups: a control group and another treated with L-tyrosine (100 mg/kg body weight). After 4 weeks, three bucks of each group were assassinated. A comparable oral dose of L-tyrosine was administered to half of the treated group left untreated during the second half. Weekly blood samples were assembled from each group for testosterone, T3, and T4 hormone testing. The results showed that body weight and serum testosterone, T3, and T4 increased exponentially with increasing age in both groups. L-tyrosine contributed to another vital rise in dose-dependence than control, in bodyweight, GSI, and testosterone, T3, and T4. At the end of the third month, tests fell in the scrotum, compared to 2 weeks before in the L-tyrosine group. In the middle of the fourth month, the semen evaluations were first carried out for the L-tyrosine group and 1 month after for the control group. L-tyrosine has contributed to a substantial upsurge in semen quality and motility, and abnormalities have reduced dramatically (P < 0.01). The L-tyrosine-treated group showed significantly increased mRNA expression of steroidogenesis markers STAR, CYP11A1, and 3B-HSD. Besides, free sperm in the seminiferous tubular lumen was discovered at the end of the third month. Nevertheless, it achieves only in control of the spermatocyte stage. The research suggests that L-tyrosine supplements promote puberty and improve male New Zealand rabbit fertility during high-temperature periods in the year.